Low-Cost Feedback Program for Reducing the Door-to-Computed Tomography Time - Takashi Mitsuhashi; Joji Tokugawa; Hitoshi Mitsuhashi (Cerebrovascular Diseases Extra, 2022)
Introduction: Early restoration of blood flow in stroke patients can be achieved by reducing the door-to-computed tomography (DTC) time. Previous research has proposed several methods to reduce the DTC time, but the implementation costs limit its transferability. This study aimed to propose a novel, simple, and low-cost method for reducing the DTC time by providing feedback on each patient’s DTC time to a small group of medical workers and physicians. Methods: A field experiment was conducted for 233 days, and the DTC time of 249 patients with stroke symptoms who were transported via ambulance to a medium-sized university hospital in Japan within 24 h after stroke onset was obtained. The first and second feedback reports on the 59th day and 154th day, respectively, were provided at the beginning of the field experiment. Using the data collected during the first 58 days as baseline data, the baseline data were compared with the post-intervention data. As part of the intervention, feedback on the DTC time for each patient was provided to six medical workers and physicians during regular meetings. The primary outcome was a continuous measure of DTC time (in min). The feedback effect hypothesis was formulated prior to data collection. Results: In a sample of 68 patients at baseline, the mean DTC time was 18.16 min with a standard deviation of 7.38 min. As a result of the two feedback reports, in the sample with outliers, the mean and standard deviation decreased to 15.64 min and 5.97 min, respectively. The difference in means was 2.51 min (p = 0.021 in t tests). Results of the test of the equality of the standard deviations suggested that the two standard deviations were not equal (p = 0.065). Conclusions: The low-cost interventions successfully reduced both the mean DTC time and variation, suggesting an improvement in the quality and consistency of medical services. The result of our fine-grained analysis with a field-experiment design supports the role of feedback in achieving early treatment as suggested in the Target: Stroke initiative.